Attitudes towards immigration and egalitarian compromises in Europe - Martín Artiles, Antonio; Meardi, Gugleilmo (Política y Sociedad, 2013)
Attitudes of European citizens towards immigrants are restrictive. Restrictive attitudes are related to the unemployment rate and the risk of poverty as well as competition for jobs and welfare resources. National policies of social protection help reduce hostility to immigration because it reduces the risk of poverty and social inequality. However, ethnic and racial heterogeneity hamper "egalitarian commitment" essential for the sustainability of the welfare state. Strong unions and social protection policies contribute to the integration of immigrants (Sweden and Norway). By contrast, weak unions, social inequalities, unemployment, the risk of poverty and weak social protection contribute to the development of negative attitudes towards immigration (Greece, Hungary). The future sustainability of welfare depends on the participation of immigration as a political force.
Keywords: Attitudes; opinion; equality; solidarity; immigration; Welfare